Protein biomarkers and microbial profiles in peri‐implantitis. Issue 9 (1st October 2015) - Wang, Hom‐Lay; Garaicoa‐Pazmino, Carlos; Collins, Amy; Ong, Hwen‐Sei; Chudri, Rini; Giannobile, William V.
Abstract: Objectives: The aim of the present investigation was to determine the profile of peri‐implant crevicular fluid (PICF) biomarkers combined with microbial profiles from implants with healthy peri‐implant tissues and peri‐implantitis to assess real‐time disease activity. Material and methods: Sixty‐eight patients were included in this cross‐sectional study. They were divided into two groups: 34 patients with at least one healthy implant (control) and 34 with at least one peri‐implantitis affected implant (test). Total DNA content and qPCR analysis for periodontal bacteria obtained from subgingival plaque samples ( Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola ) and a PICF analysis for IL‐1β, VEGF, MMP‐8, TIMP‐2, and OPG were performed. The individual and combined diagnostic ability of each biomarker for peri‐implantitis and target bacterial species were analyzed. Results: The mean concentration of IL‐1β (44.6 vs. 135.8 pg/ml; P  < 0.001), TIMP‐2 (5488.3 vs. 9771.8 pg/ml; P  = 0.001), VEGF (59.1 vs. 129.0 pg/ml; P  = 0.012), and OPG (66.5 vs. 111.7 pg/ml; P  = 0.050) was increased in the peri‐implantitis patients. The mean expression of MMP‐8 (6029.2 vs. 5943.1 pg/ml; P  = 0.454) and did not reveal a meaningful difference among groups. Total bacterial DNA of selected microorganisms was associated with a threefold or greater increase in peri‐implantitis although no statistical significant difference. The ability to diagnose diseased sites was enhanced by T. denticola combined with IL‐1β, VEGF, and TIMP‐2 PICF levels. Conclusion: The present data suggest that the increased levels of the selected PICF‐derived biomarkers of periodontal tissue inflammation, matrix degradation/regulation, and alveolar bone turnover/resorption combined with site‐specific microbial profiles may be associated with peri‐implantitis and could have potential as predictors of peri‐implant diseases.